Temporality and Memory in Architecture: Hagia Sophia - Nur, Yuksel Burcin; Ozer, Yasemen Say (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2017)
Istanbul, having hosted many civilizations and cultures, has a long and important past. Due to its geopolitical locations, the city has been the capital of two civilizations-Ottoman and Byzantine Empires-which left its traces in the history of the world. Architectural and symbolic monuments built by these civilizations made an impression in all communities making the city a center of attraction. After each and every damage caused by wars, civil strifes, and natural disasters, maximum effort has been made to restore these symbolic buildings. Attitude of a society to a piece of art or an architectural construction defined as historical artifact is shown in interventions, architectural supplementations and restorations to buildings to keep them alive. As a result of this attitude, it is accepted that buildings are perceived as a place of memory and symbolized with the city. The most important symbolic monument of the city, Ayasofya (Hagia Sophia), was found as the Church of the Byzantine Emperor in the year 360, then converted into the Mosque of the Ottoman Sultan, and now serves as one of the best-known museums of Turkey. With architectural additions requested by Byzantine emperors and Ottoman sultans, restorations and other functional changes; Hagia Sophia had become a monument witnessing its own changes as well as its surroundings while collecting memories. Accordingly, Hagia Sophia can be described as an immortal building. Immortality is out of time notion, however it is a reflection of time effects as well. Immortality is about resisting to time. A construction from the past which appreciates as time passes will also exist in the future preserving its value. The building has been strengthened with the memory phenomenon formed during construction, incidents that the building witnessed in its location, restorations, architectural supplementations and the perception of the world heritage. The main purpose of this presentation is to show how an intangible concept as memory concretizes in an architectural structure within the frames of immortality and time concepts by examining Hagia Sophia.
Keywords: Hagia Sophia; temporality; immortal building; place of memory; Architecture